Dynamic feedforward control in decoupling space for a four-degree-of-freedom parallel robot. (7th January 2019) - Song, Xiaogang; Zhao, Yongjie; Jin, Lei; Zhang, Peng; Chen, Chengwei
This article proposes a dynamic feedforward control method for a four-degree-of-freedom parallel robot in decoupling space to improve the control accuracy and robust stability. The mass matrix and the gravity component are obtained from the rigid-body dynamic model that is formulated by means of the link Jacobian matrices and the principle of virtual work. Then using the positive definiteness of the mass matrix and singular value decomposition algorithms, a decoupling transformation matrix is obtained to convert the physical joint space to the decoupling modal space. In the modal space, a decoupling closed-loop controller design has been implemented for each driven leg. Afterward, by applying the gravity component of the dynamic model, a feedforward control subsystem has been designed to compensate the influence of gravity load on the parallel robot, which can further reduce the negative impacts caused by modeling inaccuracies. This numerical simulation analysis shows that the ideal control accuracy and robust stability have been achieved using the dynamic feedforward decoupling control method for the nonlinear and strongly coupled systems of the parallel robot. The described controller has a simple structure and can be easily realized in practice.